Analysis of Feasibility Test Parameters for FTTH Access Networks with GPON Technology in the East Pontianak Perum 4 Area - Sentosa, Adi; Tjahjamooniarsih, Neilcy; Kusumawardhani, Eka (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2024)
This research employs Optisystem for evaluating network quality through calculation and simulation. It includes direct observation of installed devices at Perum 4 East Pontianak and network simulations using parameters like Power Link Budget, Rise Time Budget, BER, and Q factor. Calculations indicate that power levels on the downstream and upstream sides meet the standard. RTB analysis and BER and Q factor simulations confirm compliance with PT Panglima Kamayo Media and ITU-T G.984 standards. However, a design-implementation mismatch affects two consumers with significant power deviations, necessitating network improvements. PLB and RTB calculations on both sides confirm compliance with standards, and simulations validate the furthest network's feasibility. Yet, two specific consumers, 24 and 27, require improvements due to Prx power exceeding limits. These enhancements should consider internal and external factors, such as anthill interference. Overall, Perum 4 East Pontianak's FTTH network meets standards with potential improvements for uniformity, offering valuable guidance for PT Panglima Kamayo Media in enhancing consumer services.